Quantitative MODS-Wayne assay for rapid detection of pyrazinamide resistance in Mycobacterium tuberculosis from sputum samples - Toscano-Guerra, Emily (2024)
Tuberculosis (TB) remains a significantglobal health challenge, exacerbated by the emergence of drug-resistant strains, such as those resistant to pyrazinamide (PZA). The current scarcity of affordableand precise quantitative diagnostic tests for PZA resistance underscores the urgent need for more accessible diagnostic tools. We evaluated PZA susceptibility in 264 TB-positive samples by quantifying pyrazinoic acid (POA) production, using both the MODS-Wayne qualitative assay and our newly developed quantitative approach (MODS-WQ). The MODS-WQ was assessed in 7H9 medium (MODS-WQ7H9) or citrate buffer(MODS-WQCB), with POA levels measured via spectrophotometry against a calibration curve. PZA susceptibility determinations were based on a composite reference standard. Associations between POA levels and pyrazinamidase mutations were explored. The composite standard detected PZA resistance in 23.5% of the samples, which accounts for 62.8% of the multidrug-resistant (MDR) samples. The MODS-WQ established specificPOA cutoffsof 123.25 μM for MODS-WQ7H9 and 664.7 μM for MODS-WQCB, with sensitivities of 81.3% and 92.3% and specificitiesof 77.2% and 95.9%, respectively. Notably, samples with mutations in the pyrazinamidase metal-binding site exhibited significantlylower POA levels compared with mutations in the enzyme periphery. Furthermore, a significantcorrelation was found between POA production and PZA resistance, Bactec Growth Index, and minimum inhibitory concentration (MIC) values. This study presents a novel, direct, and accessible susceptibility test for PZA resistance that quantifiesPOA, enhancing the detection capabilities for this condition. The citrate-bufferedMODS-WQ assay demonstrated high sensitivity and specificityfor quantifying POA, confirmingthat POA production is a reliable indicator of PZA resistance.